Evaluation of Heat Loss Effect on Package Boiler Performance (5007-U) in the Utility Unit of Urea Fertilizer Industry - Rizka Wulandari Putri; M. Fabian Merdeka; Rona Alisya; Rahmatullah Rahmatullah; Muhammad Haviz (CHEESA: Chemical Engineering Research Articles, 2024)
Package boiler (PB) is a utility unit essential for producing steam by heating Boiler Feed Water (BFW) through the combustion of natural gas with air. Therefore, this study aimed to investigate the effect of heat loss on PB efficiency. To achieve this, direct and indirect methods were adopted, with data collected between 4 July and 29 August 2023. The results showed that PB efficiency in the fertilizer industry during this period ranged from 76.06% to 80.71%. On August 29, 2023, under optimal conditions, an efficiency of 80.71% was achieved, while a significant drop to 65.44% occurred during the 6th week on August 8, 2023, due to low oxygen (O2) levels. Flue gas analysis on August 29, 2023, obtained 3.64% excess O2, 11.17% carbon dioxide (CO2), and 0.04% carbon monoxide (CO). PB performance was influenced by heat loss from the dry flue gas, hydrogen (H2) content on flue gas, moisture in air and fuel, incomplete combustion, as well as radiation and convection phenomena.